The guidance club for kids - Renetzky, Alvin; Renetzky, Cheryl; Educator's Choice (Santa Monica, CA: Educator's Choice, 1992)
Designed to help youngsters acquire the skills necessary to cope with life's pressure
Narrator: Matthew R. Holzman
Keywords: Youth -- Conduct of life; Youth -- Life skill guides; Children -- Conduct of life; Parent and child; Parenting